2004
DOI: 10.1177/070674370404900808
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Course of Schizophrenia: The Madras Longitudinal Study

Abstract: E ver since Bleuler published his account of nearly a lifetime's work with schizophrenia patients (1), there has been great interest in studying the long-term course of this illness. The evolution of schizophrenia's conceptualization from dementia praecox to a heterogeneous disorder with variable outcomes has been well documented. The multinational International Pilot Study of Schizophrenia (IPSS; 2) initiated by the World Health Organization (WHO) showed that it is eminently possible to use the same standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 19 publications
6
60
0
3
Order By: Relevance
“…25 A 20-year follow-up study of the Indian cohort in the 10-nation study also showed very high level of mortality. 26 The question as to how a better symptomatic outcome at 2-year follow-ups translated to poor mortality outcomes at 5 and 20 years is an open one.…”
Section: Outcome Of Schizophreniamentioning
confidence: 99%
“…25 A 20-year follow-up study of the Indian cohort in the 10-nation study also showed very high level of mortality. 26 The question as to how a better symptomatic outcome at 2-year follow-ups translated to poor mortality outcomes at 5 and 20 years is an open one.…”
Section: Outcome Of Schizophreniamentioning
confidence: 99%
“…21 This same pattern was found at the 20-year followup. 16 Furthermore, as noted above, this cohort was subjected to high rates of mortality and suicide.…”
mentioning
confidence: 96%
“…Suicidesall by persons younger than 35 years -accounted for nearly half of all deaths (7 of 16). 16 The paradox of a better symptomatic outcome in developing countries was also exemplified in the results of the earlier IPSS. 17 Even though a better 2-year clinical outcome was reported for patients from developing countries, at the 5-year follow-up, the percentages of patients in Agra (India) and Ibadan (Nigeria) who had died were 9.0 and 7.1, respectively, compared with 4.9% for the entire study cohort.…”
mentioning
confidence: 98%
“…Si bien esta idea ha sido discutida 40 , la hipótesis sociocultural ha generado un interesante campo de investigación para epidemió-logos y etnógrafos 41,42 . Hoy por hoy podemos hablar de cuatro líneas de estudio que, si bien no son excluyentes ni contradictorias entre sí, pueden descomponerse a efectos analíticos.…”
Section: El Dilema De La Diferencia En El Pronóstico De Enfermedades unclassified